Human development report 1999. (Oxford University, 1999)
Human Development Report 1999 aims to present the relation between consumption and human development. World consumption during the 20th century has grown at an unprecedented rate, reaching about $24 trillion in 1998. Consumption growth has brought its own problems - inequality, environmental stresses, and adverse social impacts from rising pressures for competitive spending. Human Development Report 1998 reviews the challenges that all people and all countries face - to forge consumption patterns that are more environmentally friendly, more socialy equitable, that meet basic needs of all and that protect consumer haelth and safety.